Russian Peacekeeping Strategies in the CIS - Lynch, D. author. aut Link
XI, 265 p.
Keywords: Peacekeeping operations have become a central issue in international relations since the end of the Cold War. This work underlines the mixture of defensive and offensive stimuli driving Russian 'peacekeeping' strategies, and highlights the dangers that the new Russian Federation faces in undertaking these operations.